Association Between the Right Ear Advantage in Dichotic Listening and Interaural Differences in Sensory Processing at Lower Levels of the Auditory System in Older Adults. Issue 5 (September 2021) - Ianiszewski, Alejandro; Fuente, Adrian; Gagné, Jean-Pierre
Abstract : Objective: Current evidence suggests that an enhanced right ear advantage (REA) in dichotic listening (DL) among older adults may originate from age-related structural changes in the corpus callosum and age-related decline in cognitive processes. Less is known about the effect of information processing at lower portions of the auditory system on DL performance. The present study investigates whether interaural differences (ID) in sensory processing at lower levels of the auditory system are associated with the magnitude of the REA in DL among older adults. Design: Sixty-eight older adults participated in the study. Participants were assessed with a DL test using nonforced (NF) and forced attention paradigms. Hearing sensitivity, transient-evoked otoacoustic emission (TEOAE), contralateral suppression of TEOAE, a proxy measure of medial olivocochlear activation, and auditory brainstem response to speech stimuli (speech-ABR) were tested in both ears separately. The ID in sensory processing at lower levels of the auditory system was derived by calculating the difference between the RE and LE for each auditory measure. Bivariate and multivariate regression models were performed. One multivariate model for each DL paradigm (NF and forced attention) was independently constructed. Measures of cognitive speed of processing and cognitive flexibility were accounted for in the regression models. Results: For both multivariate regression models, ID in pure-tone thresholds and ID in MOC suppression of TEOAE were significantly associated with the magnitude of the REA for DL among older adults. Cognitive measures of speed of processing and cognitive flexibility also contributed to the magnitude of the REA. Conclusion: These results suggest that ID in sensory processing at lower levels of the auditory system account, at least in part, for the increased magnitude of the REA in DL among older adults. Abstract : Supplemental Digital Content is available in the text.